Kultivasi rumput laut Caulerpa lentillifera menggunakan berat awal berbeda dengan metode rawai permukaan - Mamesah, Jeivana F.T; Mudeng, Joppy D.; Ngangi, Edwin L. A.; Kreckhoff, Reni L.; Salindeho, Indra R.N.; Sambali, Hariyani; Mokolensang, Jeffrie F. (e-Journal BUDIDAYA PERAIRAN, 2025)
The research purposes were to determine the best initial weight of Caulerpa lentillifera algae, determine the appropriate cultural operational depth for the best growth of C.lentillifera algae, and determine the interaction between the initial weight factor of C.lentillifera algae and the depth factor of growth. This research was carried out from May to July 2023. The C. lentillifera algae in this research were obtained from nature. C.lentillifera algae culture is carried out using the verticulture method, namely tying the algae to strings arranged in a row. This research was designed using a 3x3 factorial in a Completely Randomized Design (RAL). There are 2 factors tested in this experiment, each of which has 3 levels, namely: the weight factor of C. lentillifera algae which consists of: A1 = 50 grams, A2 = 100 grams and A3 = 150 grams, and the depth factor which consists of: B1 = 20 cm, B2 = 70 cm and B3 = 120 cm. The results obtained from this research are that differences in the growth of C. lentillifera algae are very significantly influenced by differences in the initial weight of different. The best absolute growth, relative growth, and daily growth rate were initial C. lentillifera algae weights of 50 grams, which respectively had the highest average values of 24.3 grams, 16.2%, and 1.4%. Differences in depth had no significant influence on differences in absolute growth, relative growth, and daily growth rate of the algae C. lentillifera. The results of variance analysis showed that the influence of the weight factor of C. lentillifera on absolute growth, relative growth, and daily growth rate did not change significantly when the depth factor level was changed. Keywords: verticulture; growth; initial weight; depth